Balancing strength and ductility in AA7075 through controlled heat treatment parameters - Lay, Sheng Ewe; Weng, Kean Yew; Alazzani, Emadaddin Abdo; Nor Zakiah Gorment; Balasubramani, Senthil Rathi (Penerbit Universiti Kebangsaan Malaysia, 2026)
AA7075-T6 aluminium alloy, known for its high strength-to-weight ratio, is an ideal material for many industries, such as aerospace and structural engineering. However, its mechanical performance is highly sensitive to heat exposure, and inconsistent heat treatment practices across industries have resulted in varying performance outcomes. Despite the alloy’s importance, there is limited empirical data that systematically correlates specific heat treatment parameters with resulting mechanical properties. This study addresses this gap by investigating the effects of post-treatment heat exposure at 425 °C, 450 °C, and 475 °C for durations of 30 min and 60 min. Mechanical testing showed that tensile strength decreased from 600 MPa in the T6 condition to as low as 377 MPa after treatment at 425 °C for 60 min. Similarly, yield strength dropped from 540 MPa to 199 MPa under the same conditions. Hardness declined from approximately 91 HRB in the untreated state to 55 HRB after extended exposure. In contrast, elongation improved from 13.2% in the original condition to a maximum of 22.5%, indicating increased ductility. Young’s modulus remained stable at approximately 16.3-17.3 GPa across all heat-treatment conditions. These results show the importance of controlled heat treatment to maintain strength while improving ductility, providing useful understanding for optimizing AA7075 in demanding applications.